The cross-talk of lung and heart complications in COVID-19: Endothelial cells dysfunction, thrombosis, and treatment - Liu, Langjiao; Jing, Haijiao; Wu, Xiaoming; Xiang, Mengqi; Novakovic, Valerie A.; Wang, Shuye; Shi, Jialan (Frontiers in Cardiovascular Medicine, 2022)
SARS-CoV-2 was initially thought to be a disease affecting the lungs during the pandemic, but as data updated, it was found to also involve the heart system. More seriously, it can cause cardiopulmonary sequelae after infection. However, the link between cardiopulmonary complications remains unclear. Thrombosis of endothelial cells dysfunction has become an uncontroversial mechanism. Its role in stimulating platelet activation and thrombotic inflammation has been widely reported. But the procoagulant role of microparticles (MPs) in COVID-19 seems to be neglected. As membrane vesicles released after cell injury or apoptosis, MPs exert procoagulant activity mainly by exposing phosphatidylserine (PS) on their surface. It can provide a catalytic surface for the assembly of the prothrombinase complex. Therefore, inhibiting PS externalization is a potential therapeutic strategy. In this paper, we describe the pathophysiological mechanism of SARS-CoV-2 inducing heart and lung complications through injury of endothelial cells, emphasize the procoagulant effect of MPs and PS, and propose the significance and basis of early antithrombotic therapy. In addition, hypoxia is an indispensable factor in the mechanism of SARS-CoV-2-induced endothelial cells injury, which is also a serious manifestation of pulmonary symptoms. This article will also describe its mechanism in detail and support oxygen therapy. In the case of SARS-CoV-2 infection, virus invades endothelial cells through direct infection, hypoxia, imbalance of the RAAS, and cytokine storm. These factors cause endothelial cells to release MPs, form MPs storm, and eventually lead to thrombosis. In turn, thrombus accelerates hypoxia and cytokine storms, forming a positive feedback regulation. Given the important role of thrombosis in the disease, early antithrombotic therapy is an important tool for COVID-19. It may maintain normal blood circulation, accelerating the clearance of viruses, waning the formation of MPs storm, and avoiding disease progression.